2013
DOI: 10.1038/icb.2013.38
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of tumor‐specific CD8+ CTLs by tumor‐infiltrating tolerogenic dendritic cells

Abstract: Cancer immunosurveillance failure is largely attributed to the insufficient activation of tumor-specific class I major histocompatibility complex (MHC) molecule (MHC-I)-restricted CD8+ cytotoxic T lymphocytes (CTLs). DEC-205+ dendritic cells (DCs), having the ability to cross-present, can present captured tumor antigens on MHC-I alongside costimulatory molecules, inducing the priming and activation of tumor-specific CD8+ CTLs. It has been suggested that reduced levels of costimulatory molecules on DCs may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 32 publications
2
78
0
1
Order By: Relevance
“…We confirmed that these cells showed similar antigenicity as well as identical surface class I MHC molecule restriction 21. The original Hepa1‐6‐1 cells showed continuous growth after s.c. implantation into syngeneic B6 mice and did not prime CD8 + CTLs, whereas the Hepa1‐6‐2 cells failed to grow in vivo by Hepa1‐6‐2‐specific CD8 + CTLs, which also efficiently eliminated Hepa1‐6‐1 cells in vitro 11. Therefore, we first established Hepa1‐6‐2‐specific CD8 + CTLs through the repetitive stimulation of Hepa1‐6‐2‐primed spleen cells with Hepa1‐6‐2 tumour cells in vitro and confirmed that these cells specifically killed both Hepa1‐6‐1 and Hepa1‐6‐2 cells in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We confirmed that these cells showed similar antigenicity as well as identical surface class I MHC molecule restriction 21. The original Hepa1‐6‐1 cells showed continuous growth after s.c. implantation into syngeneic B6 mice and did not prime CD8 + CTLs, whereas the Hepa1‐6‐2 cells failed to grow in vivo by Hepa1‐6‐2‐specific CD8 + CTLs, which also efficiently eliminated Hepa1‐6‐1 cells in vitro 11. Therefore, we first established Hepa1‐6‐2‐specific CD8 + CTLs through the repetitive stimulation of Hepa1‐6‐2‐primed spleen cells with Hepa1‐6‐2 tumour cells in vitro and confirmed that these cells specifically killed both Hepa1‐6‐1 and Hepa1‐6‐2 cells in vitro (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The murine hepatoma cell lines Hepa1‐6‐1 and Hepa1‐6‐2 were established from Hepa1‐6 11. Briefly, Hepa1‐6‐1 cells were obtained from the purified cells of a collagenase‐digested and surgically removed tumour mass that was grown for approximately 3 months after the s.c. implantation of Hepa1‐6 cells into syngeneic B6 mice and were maintained in D‐10 medium.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations